Zaslužni profesor dr. Ivan Kristan (1930-2023) - Cerar, Miro (Pravnik, 2023)
The contribution is an obituary for Professor Emeritus Ivan Kristan, PhD, of the University of Ljubljana. His extensive knowledge and experience nurtured several generations of Slovenian lawyers, guiding both their personal and professional growth. His profound and dedicated professional, scientific, and public activities markedly advanced Slovenian legal science and society at large. Amongst his many roles, he served as the Dean of the Faculty of Law in 1981–1985, and the 34th Rector of the Edvard Kardelj University in Ljubljana between 1985 and 1987. His distinguished career led him to the Constitutional Court of the SFR Yugoslavia in Belgrade in 1987-1991. In these turbulent years, particularly 1990 and 1991, he opposed some constitutionally controversial proposals and decisions in decision-making and with his separate opinions. Notably, Professor Kristan objected to a proposal designed to prevent the adoption of the Slovenian constitutional amendments, which substantiated the elements of Slovenian sovereignty. At that time, the Yugoslav Constitutional Court, with Professor Kristan’s insistence, remained the sole federal state body that did not condemn these amendments in advance. He demanded compliance with the regulations stipulating the Constitutional Court’s lack of competence for preliminary constitutional review. Between 1992 and 1997 he was also the first president of the State Council of the Republic of Slovenia.
Keywords: biografije; Kristan, Ivan; nekrologi; slovenski pravniki; ustavno pravo